Ownership Identity And Capital Structure: A Panel Analysis For Quoted Firms In Kenya - Muthoni, George Gikama; Nasieku, Tabitha Merepei (Advances in Social Sciences Research Journal, 2018)
The objective of this paper was to determine the relationship between ownership identity and capital structure of non-financial firms listed on the NSE. The target population was 42 firms, however, only 35 firms had consistency of data for a balanced panel regression for the period 2008-2017. The study adopted longitudinal quantitative research design with random-effects GLS model. The ownership identity was measured using managerial, institutional, government and retail ownerships while capital structure was measured using leverage ratio. The analysis show that the relationship between capital structure and managerial ownership was positive and statistically insignificant while Institutional ownership was found to be positive and significant. In addition, Government ownership was found to be negatively insignificant and lastly, Retail ownership was found to be negatively and insignificantly related. This study recommends that there is need to nurture a good relationship with all institutional investors such as banking companies, insurance companies, pension funds, trust funds and mutual funds to benefit from the pool of expertise they engage to do investment and financing researches. Finally, since there is prospect for East African regional integration, an examination of ownership structure and leverage within East African Community Countries ought to be investigated.